Youth Empowerment and High School Gay-Straight Alliances - Russell, Stephen T. (2009)
In the field of positive youth development programs, “empowerment” is used interchangeably with youth activism, leadership, civic participation and self-efficacy. However, few studies have captured what empowerment means to young people in diverse contexts. This article explores how youth define and experience empowerment in youth-led organizations characterized by social justice goals: high school Gay-Straight Alliances (GSAs). Through focus group interviews, fifteen youth leaders of GSAs from different regions of California explain what they think empowerment means and how they became empowered through their involvement with the GSA. Youth describe three inter-related dimensions of empowerment: personal empowerment, relational empowerment, and strategic empowerment through having and using knowledge. When these three dimensions are experienced in combination, GSA leaders have the potential for individual and collective empowerment as agents of social change at school. By understanding these youth's perspectives on the meanings of empowerment, this article clarifies the conceptual arena for future studies of socially marginalized youth and of positive youth development.